(untitled) (LEARNing Landscapes, 2008)
This article explores the relationships between learning and teaching, and focuses on challenges for the future, which include the integrity of research, not only in academia but also in other fields, arising from the developments in the field of information technology. It suggests that learning and teaching need to be combined with principled leadership and the establishment of fundamental values.